Childhood Hearing Loss in the Developing World - Störbeck, Claudine (International Journal of Child Health and Nutrition, 2012)
Globally, unidentified hearing loss is the largest and most significant childhood disability impacting on development. Of the babies born annually with hearing loss, 90% come from developing countries. Less than 2.5% of these babies will get hearing aids and less than 10% will ever have access to early intervention. With the dearth of services available to this largely marginalized paediatric community, the EHDI pathway has been established with significant buy in from the World Bank, WHO and UNESCO. This paper will explore the EHDI pathway and how it is currently being implemented in the developing world.